The impacts of stimulation in protracted labor to cortisol levels and incidence of post-partum blues - Soetrisno, Soetrisno; Respati, Supriyadi Hari; Sulistyowati, Sri; Kurniawan, Hendro (Folia Medica Indonesiana, 2017)
Delivery, induction, stimulation, cesarean section with the aid of a vacuum extraction, for example, can reduce maternal confidence on the smooth delivery process, as well as improve postpartum stress. These stressors stimulate the HPA axis (hypothalamus-pituitary-adrenal), so that the adrenal cortex produces more cortisol hormone, it can increase postpartum blues. The objective of this study was to analyze the effect of delivery stimulation on protracted labor on cortisol levels and the occurrence of postpartum baby blues. This was an experimental study of non-randomized post-test control group. The subject of the study 30 patients in labor taken consecutive sampling, divided into 2 groups (normal delivery and stimulation) each group consist of 15 patients. In stimulation delivery group, it is examined of cortisol serum levels after five days and then continued for postpartum blues occurrence measurement. Statistical analysis using t-test for differences in levels of cortisol and chi square for analyzing the effect on the occurrence of post-partum blues (a=0.05). Mean level of cortisol in delivery stimulation group is 40.29 ± 5.58, in normal delivery is 33.59 ± 11.17, with p=0.047, meaning there are significant differences both study groups. Stimulation delivery increases the occurrence of post-partum blues 5.50 times compared to normal delivery (OR=5.50 and p=0.028). Mean cortisol levels on post-partum blues higher at 42.90 ± 6.97 compared to no post-partum blues 30.14 ± 6.66, p=0:00, which means there are significant differences both groups. In conclusion, there was significant relationship between stimulation in protrated labor that increases cortisol serum level and post partum blues incidence.